2021
DOI: 10.1186/s12935-021-01767-5
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000020 elevates the expression of PIK3CA and facilitates the malignant phenotypes of glioma cells via targeting miR-142-5p

Abstract: Background Multiple circular RNAs (circRNAs) have been recently described as crucial oncogenic factors or tumor suppressors. This study aimed to investigate the role of circ_0000020 in glioma progression. Methods Circ_0000020 and miR-142-5p expressions in glioma samples were assessed through qRT-PCR, and then the association between pathological indexes and circ_0000020 expressions was analyzed. Functional experiment was performed with human glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…MORC2 is highly expressed in human glioma cells compared with normal glial cells. Human glioma cell lines have been used widely in studies of glioma pathogenesis (14)(15)(16). First of all, the expression of MORc2 in several human glioma cell lines (U251, SHG44, LN229 and T98G) was determined using RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…MORC2 is highly expressed in human glioma cells compared with normal glial cells. Human glioma cell lines have been used widely in studies of glioma pathogenesis (14)(15)(16). First of all, the expression of MORc2 in several human glioma cell lines (U251, SHG44, LN229 and T98G) was determined using RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely accepted that CircRNA-miRNA network has a close relationship with osteogenic differentiation [ 18 ]. In a recent study, it was reported that Circ_0000020 promotes glioma cell growth, and links with poor prognosis [ 19 ]. However, the role of Circ_0000020 in regulating osteogenic differentiation is not studied well.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that circRNA_104348 can promote hepatocellular carcinoma progression by modulating the miR-187-3p/RTKN2 (Rhotekin 2) axis 12 . Circ_0000020 can elevate the expression of PIK3CA (phosphatidylinositol 3-kinase C) and facilitate the malignant phenotypes of glioma cells by targeting miR-142-5p 13 . An increasing number of circRNAs have been found to be unbalanced in LUAC and can be used as therapeutic targets in the future.…”
Section: Introductionmentioning
confidence: 99%